e-WoM di Mom Travel Blog: Keterikatan, Pengaruh Informasi, dan Kekuatan Informasi Visual - Puspitasari, Kunti (Faculty of Communications Science, Dr. Soetomo University, 2021)
The Social Networking System (SNS) is used to share messages through electronic WoM (e-WoM) through blogs. Related to someone in e-WoM has a social construction motivation that involves tie strength and informational influence. This article analyzes how attachment, informational influence, the power of visual information in e-WoM user engagement on mom travel blogs can determine travel preferences and decisions for families. In addition to conducting a literature ulasan, this article also analyzes Mom Travel Blogs in Indonesia, namely jalanjalankenai.com and momtraveler.com. These blogs found that the social relationship between the reader and the blogger is an attachment that motivates involvement in e-WoM on the blog. These blogs also provide informational influence and present the power of visual information to convince readers of travel preferences.